+0

0
80
1

Let \$f(x) = 2x + 7\$ and \$g(x) = 3x + c\$. Find \$c\$ if \$(f \circ g)(x) = (g \circ f)(x)\$ for all \$x\$.

Guest Jul 24, 2017
Sort:

#1
+4174
+1

Find  c  if  f( g(x) )  =  g( f(x) )  for all  x  .

f(x)  =  2x + 7                          To find  f( g(x)  ) , replace every instance of  x  with  g(x)  .

f( g(x) )  =  2( g(x) ) + 7             Since  g(x)  =  3x + c  , we can write...

f( g(x) )  =  2( 3x + c ) + 7

g(x)  =  3x + c                         To find  g( f(x) ) , replace every instance of  x  with  f(x)  .

g( f(x) )  =  3( f(x) ) + c              Since  f(x)  =  2x + 7  , we can write...

g( f(x) )  =  3( 2x + 7 ) + c

We want to know what  c  is when

f( g(x) )  =  g( f(x) )                                   Substitute the functions in.

2( 3x + c ) + 7  =  3( 2x + 7 ) + c

6x + 2c + 7  =  6x + 21 + c                    Subtract  6x  from both sides.

2c + 7  =  21 + c                                    Subtract  c  from both sides, and subtract  7  from both sides.

c  =  14

hectictar  Jul 24, 2017

### 16 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details